PERKEMBANGAN JUMLAH PENDERITA TYPHOID FEVER DI RSU STELLA MARIS TELUKDALAM - Deswidya S Hutauruk; Ester Deslyn Ndruru; Elsida Aritonang; Sri Rahma Friani (Yayasan Nusantara Hasana Berdikari, 2025)
Typhoid fever is a type of bacterial infection of Salmonella typhi which attacks the digestive tract and enters the digestive tract with unhygienic food and drinks. Symptoms of typhoid fever include prolonged fever, fatigue, headache, nausea, diarrhea and constipation. This study aims to determine the development of typhoid fever in Stella Maris Telukdalam Hospital. The type of research used is descriptive observational research with secondary data collection. The results showed there were 78 cases of Typhoid fever consisting of 46 female patients and 32 male patients. Typhoid fever cases are most commonly found in the pediatric age group, especially in the age range of 5-14 years and have increased from October to December. Typhoid fever sufferers are more men than women, this is because men often move outside the home. Based on age more sufferers in the age group of children this is related to immunity that is not yet strong, hygiene, not washing hands after playing outside the home. It can be concluded that the development of typhoid patients at Stella Maris Hospital is still high in men, children's age and the range of typhoid in the rainy season.